Green Synthesis of ZnO NPs Using Chamomile Flower Extract Via Pulsed Laser Ablation and Its Effect on Surface Wounds - Abbas, Sarah A.; Mazhir, Sabah N. (Iraqi Journal of Science, 2026)
Zinc oxide (ZnO) plays a pivotal role across various industries due to its remarkable properties, which are further enhanced when engineered at the nanoscale. In recent years, the green synthesis of nanoparticles using biological systems, particularly plant extracts, has emerged as a rapidly advancing field within nanotechnology. This eco-friendly approach aims to reduce the environmental impact associated with conventional methods. In the present study, zinc oxide nanoparticles (ZnO NPs) were synthesized using zinc oxide and an aqueous extract of chamomile flowers as a reducing and stabilizing agent. The field emission-scanning electron microscopy (FESEM) results of ZnO pure and ZnO green, respectively, showed that the shape of the nanoparticles is semi-spherical, and the nano size ranges between 20nm and 50nm, and atomic force microscopy (AFM) provided detailed information on the topographical features at the nanoscale. Together, these characterization techniques confirmed the successful synthesis of ZnO NPs, highlighting the potential of green synthesis methods in producing nanoparticles with desirable properties for biological applications. The ZnO NPs were made utilizing an eco-friendly technique using extracts of chamomile flower (Matricaria chamomilla L.) and showed their direct effect on healing the surface wounds in mice.